2016
DOI: 10.2147/ndt.s111131
|View full text |Cite
|
Sign up to set email alerts
|

The interactive effects of ketamine and magnesium upon depressive-like pathology

Abstract: Approximately one-third of patients with major depressive disorders (MDDs) are resistant to current treatment methods, and the majority of cases relapse at some point during therapy. This has resulted in novel treatments being adopted, including subanesthetic doses of ketamine, which affects aberrant neuroplastic circuits, glutamatergic signaling, and the production of brain-derived neurotrophic factor. Ketamine rapidly relieves depressive symptoms in treatment-resistant major depressive disorder patients with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…In preclinical studies, magnesium administered together with a low dose NMDA antagonist caused a reduction in depressive-like behaviors during the animal depression model test-FST (forced swim test) in mice [17,19]. One animal study hypothesized about magnesium potentially being a co-factor that would increase the effect of ketamine but not confirm the usefulness of magnesium as a supportive treatment for ketamine in depression in mice [7]. Other studies suggested magnesium supplementation to antidepressants-such as imipramine, fluoxetine, citalopram, tianeptine, and bupropion-resulted in a synergistic antidepressant effect in FST paradigm [20,21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In preclinical studies, magnesium administered together with a low dose NMDA antagonist caused a reduction in depressive-like behaviors during the animal depression model test-FST (forced swim test) in mice [17,19]. One animal study hypothesized about magnesium potentially being a co-factor that would increase the effect of ketamine but not confirm the usefulness of magnesium as a supportive treatment for ketamine in depression in mice [7]. Other studies suggested magnesium supplementation to antidepressants-such as imipramine, fluoxetine, citalopram, tianeptine, and bupropion-resulted in a synergistic antidepressant effect in FST paradigm [20,21].…”
Section: Discussionmentioning
confidence: 99%
“…Current antidepressant treatment (ADT) includes drugs exhibiting a homogeneous mechanism of action mainly related to the regulation of the monoaminergic systems, with unmet needs in non-monoaminergic mechanisms of action [2,4]. Pathophysiology of depression is complex and it also incorporates glutamatergic system and magnesium ions imbalance [5][6][7].…”
Section: Introductionmentioning
confidence: 99%